Measuring Health Literacy among seniors: validation of the European Health Literacy Survey Questionnaire 6 in the Tuscan PASSI sample - Bonaccorsi, Guglielmo; Zanobini, Patrizio; Biagi, Claudia; Volpi, Michele; Possenti, Valentina; Minardi, Valentina; Masocco, Maria; Mereu, Giovanna; Cecconi, Rossella; Garofalo, Giorgio; Lorini, Chiara (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The demographic transition has led to an increase in the older population, resulting in a rise in individuals with comorbidities and reduced self-sufficiency. Low health literacy levels are associated with poor health outcomes especially among vulnerable groups (like older individuals). Enhancing health literacy through targeted programs is crucial for improving self-care in chronic conditions. To date, in Italy, there are no validated tools to measure health literacy in older people. Thus, the aim of this study is to validate the European Health Literacy Survey Questionnaire 6 in a Tuscan (Italy) sample of senior individuals. Study design. Cross-sectional. Methods. The sample was drawn from the Surveillance System of Advancements in health of the Italian Local Healthcare Units from 2017 to 2019. Item analysis, Cronbach’s alpha and confirmatory factor analysis were used to validate the scale. Additionally, associations between Health Literacy levels and sociodemographic characteristics were analyzed. Results. A total of 11,000 subjects were interviewed, with 1,080 (10%) aged 65-69. Cronbach’s alpha was 0.89. In the older subgroup, the percentage of missing responses ranged from 4.54% to 11.85%, with the fourth item having the highest percentage of missing values. The confirmatory factor analysis revealed that the three-factor model showed a better fit to the data compared to the unidimensional model. Similar findings were observed in the 18-65-year-old population. In both groups, individuals with economic difficulties or lower education were at higher risk of having inadequate levels of health literacy. Moreover, in the 18-64 age group, being female reduced the probability of having an inadequate health literacy level, while being inactive/retired or a foreigner increased it. Conclusions. The study provides preliminary evidence supporting the validity and reliability of the European Health Literacy Survey Questionnaire 6 for assessing health literacy in the Italian older population. Further research is necessary to confirm these findings, particularly in samples of individuals aged over 69 years.